Health-Business Ethics: Oxymoron or Pleonasm? - Raouf JAZIRI; Saleh Alnahdi (Communications of International Proceedings, 2024)
Health and healthcare activities consistently have business aspects, contributing to the emergence of many dialogic and polyphonic concepts such as health-business, healthcare-business, and medical-business. This greater rapprochement between business, health, and healthcare lead to the rise of ethical issues related to their professional practices. The debate over whether health and business ethics should be compatible or not has been a subject of discussion for an extended period. There is a growing trend in business and health fields towards a stronger connection between the constructed word health-business and ethics. The purpose of this paper is to provide an overview of several aspects of this important problem and to examine the ethical implications of health and healthcare as a business. We investigate the effective integration of business ethics and profitability in the operations of healthcare organizations. Based on a qualitative approach, we try to demonstrate that health-business ethics is not an oxymoron, but rather a pleonasm promoting a new paradigm.
Keywords: Business ethics; health ethics; health-business; oxymoron; pleonasm.